Environmental flows stimulate estuarine plankton communities by altered salinity structure and enhanced nutrient recycling. (5th December 2022) - McNaughton, Caitlyn; Cook, Perran L.M.; Wong, Wei Wen; Koster, Wayne M.; Reich, Paul; Jenkins, Gregory P.; Cartwright, Ian; Beardall, John; Woodland, Ryan J.
Abstract: Sustainable management of estuaries depends on understanding the synergistic effects of nutrients and hydrological factors on estuarine food webs. We examined how phytoplankton, zooplankton and selected fish larval counts ( Acanthopagrus butcheri, black bream) vary in relation to groundwater inputs and environmental flow releases (EFRs) in a small, highly flow-regulated estuary (Werribee, Victoria, Australia). We found that groundwater-derived nutrients and an EFR were associated with the community structure of phytoplankton and zooplankton and abundance of fish larvae. Elevated phytoplankton concentration was associated with increased flagellate abundance (genus Euglena ), followed by increased abundance of diatoms ( Cyclotella sp). The latter increase was primarily associated with groundwater-derived nitrate entering the estuary. Cyclotella sp. abundance collapsed following an EFR and the subsequent increase in ammonium (NH4 + ) concentrations in the estuary. In addition, the strong halocline and increased bottom water NH4 + concentrations resulting from the EFR appeared to stimulate population growth of flagellate taxa and calanoid copepods. The abundance of calanoid copepodites and nauplii, which are the preferred food for larval A. butcheri, greatly increased due to the EFR, and was associated with an increase in larval A. butcheri abundance at this time. This effect of the EFR on the cascading trophic interactions in the estuarine food web has rarely been shown. Our study reinforces the ecological linkages between freshwater inputs, including groundwater and riverine discharge, and estuarine biotic community structure and function. Importantly, this study underscores the potential food web consequences of freshwater flow manipulation into estuaries and provides evidence for using environmental flows to enhance and/or manage the recruitment of estuarine fishes. Highlights: Groundwater and environmental flow releases (EFR) altered an estuarine community. A diatom bloom was associated with groundwater-derived nitrate entering the estuary. EFR stimulated population growth of flagellates, calanoid copepods and fish larvae. Documented EFR effects on cascading trophic interactions in estuaries are rare. This study provides evidence of EFR enhancing the productivity of estuarine fishes.